Obesity and adiposity indicators in asthma and allergic rhinitis in children. Issue 1 (February 2019) - Tajima, Hanako; Pawankar, Ruby
Abstract : Purpose of review: The prevalence of obesity and allergic diseases, such as asthma and allergic rhinitis, is increasing worldwide not only in adults, but also in children. Experimental and clinical studies have demonstrated the effect of obesity not only on asthma, but also on other allergic diseases. Recent findings: Allergic diseases, such as asthma and allergic rhinitis, are common chronic inflammatory diseases of the airways. Obesity is an increasingly common pediatric disease and is a risk factor for the development of asthma in that obese patients with asthma tend to have more severe asthma that does not respond well to standard asthma therapy. On the contrary, children with asthma maybe at a high risk of obesity, suggesting that the relationship of asthma and obesity seems to be interrelated. The role of obesity on the development of allergic rhinitis is not well defined, whereas allergic rhinitis may have an impact on obesity. Summary: Childhood obesity is often considered to be less serious than obesity in adults because of the greater risk of complications in obese adults. In this review, we discuss the allergic confounders of obesity and the impact of allergic diseases on obesity. Proper control of the BMI within the normal range in children with allergic diseases is important.